Grape Polyphenols to Arrest in Vitro Proliferation of Human Leukemia Cells: A Systematic Review and Meta-analysis - García Martínez, Daniel J.; Calzada Funes, Javier; Martín Saborido, Carlos; Santos, Cruz (My University, 2022)
.

Leukemia is a heterogeneous group of hemopoietic cancers, which accounts for 2.6% of new cases per year of total cancer incidence worldwide. Grapes and grape-derived products, such as grape juice, are naturally rich in polyphenols, bioactive compounds with antioxidant properties. Certain polyphenols have been proved to alter oxidative balance, both in inducing apoptosis in cancer cells and in preventing cancer development via controlling oxidative stress. To assess the therapeutic potential of grape polyphenols in the treatment of leukemia, a systematic review and meta-analysis of the reported data on leukemia was carried out. Following the PRISMA guide, a literature review of published papers on leukemia and polyphenols from the last 50 years was conducted, and 17 scientific articles published from 2002 to 2017 were included in the study. Resveratrol 50 μM had the highest growth inhibition effect (67%) followed by quercetin (30%). The results also point to a differential effect of polyphenols based on cell lineage; monocytes- and myelocytic-derived cell lines are the most susceptible, with a mean of 85% and 64% proliferation inhibition, respectively. Moreover, results show that growth inhibition cannot be associated with a molecular effect of polyphenols on the cell cycle arrest.
Artículos en revistas